2010
DOI: 10.1016/j.jpainsymman.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Congruence Between Preferred and Actual Place of Death

Abstract: Congruence between preferred and actual place of death may be an essential component in terminal care. Most patients prefer a home death, but many patients do not die in their preferred location. Specialized (physician, hospice and palliative) home care visits may increase home deaths, but factors associated with congruence have not been systematically reviewed. This study sought to review the extent of congruence reported in the literature, and examine factors that may influence congruence. In July 2009, a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
126
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 37 publications
10
126
2
4
Order By: Relevance
“…However, given the data that indicate relatively late hospice enrollment, unrelieved suffering at the end of life, 1 and the discrepancy between the numbers of Americans preferring to die at home and those who do, 26 it is clear that important care needs go unmet for many. Understanding the process of transition from cure-focused to comfort-focused care from the perspective of patient-caregiver dyads can inform provider actions to assist those for whom a transition to comfort care is the best choice.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the data that indicate relatively late hospice enrollment, unrelieved suffering at the end of life, 1 and the discrepancy between the numbers of Americans preferring to die at home and those who do, 26 it is clear that important care needs go unmet for many. Understanding the process of transition from cure-focused to comfort-focused care from the perspective of patient-caregiver dyads can inform provider actions to assist those for whom a transition to comfort care is the best choice.…”
Section: Discussionmentioning
confidence: 99%
“…19 These data demonstrated discrepancies between the rates of actual and preferred place of care and death, which were similar to those in developed countries as summarized by recent reviews. [20][21][22][23] Almost 80% of Japanese people actually spent time and died in a hospital, instead of their different preferred place of care in their end-of-life stage. Studies revealed that the preferences for end-of-life care and death change with one's personal life experience.…”
Section: Discussionmentioning
confidence: 99%
“…3 Preferences for place of care are rarely clearly differentiated from place of death. 15 When they are, preference for care at home is greater than for death at home. 6 10 13 24 As with the evidence from public surveys, it seems that although patients may specify home as their preferred place, location may not be a high priority, 15 especially in comparison to freedom from distress and pain.…”
Section: Is Place Of Death a Public Priority?mentioning
confidence: 99%
“…15 When they are, preference for care at home is greater than for death at home. 6 10 13 24 As with the evidence from public surveys, it seems that although patients may specify home as their preferred place, location may not be a high priority, 15 especially in comparison to freedom from distress and pain. 4 10 18 22 Qualitative evidence indicates that patient attitudes to place of death are complex, uncertain, shifting, and pragmatic.…”
Section: Is Place Of Death a Public Priority?mentioning
confidence: 99%